THE EFFECT OF THINK TALK WRITE (TTW) STRATEGY ON STUDENTS’ ABILITY IN WRITING DESCRIPTIVE TEXT - Srimaharani Tanjung; Wiki Tedi Rahmawati; Harahap Harahap (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This research aimed to find out the effect of Think Talk Write (TTW) Strategy on students’ ability in writing descriptive text. The research was conducted by using experimental research design. The population was the students of grade X consisting of 60 students. The sample was selected by applying cluster random sampling technique. The sample was divided into two groups namely experimental and control groups. Class X-iis consisting of 30 students was the experimental group taught by using Think Talk Write (TTW) Strategy. Class X-mia consisting of 30 students was the control group taught by conventional strategy. The instrument used to collect the data was writing test. The result of the data analysis by applying t-test formula showed that t-obs value was higher than t-table value (t-obs > t-table = 3.747 > 2.660). Based on the finding, Ha was accepted and Ho was rejected. Thus, Think Talk Write (TTW) Strategy significantly affected the students’ ability in writing descriptive text.